Granulomatosis with polyangiitis (Wegener's granulomatosis) diagnosed by transbronchial biopsy from stenotic portion of mainstem bronchus. Issue 4 (July 2015) - Sendo, Sho; Tsuji, Goh; Umeda, Ryosuke; Ichise, Yoshihide; Kumagai, Shunichi; Suzuki, Yujiro
Abstract This report concerns a case of granulomatosis with polyangiitis (GPA) (Wegener's granulomatosis (WG)) with bronchus narrowing. Although nasal biopsy had been performed three times, no positive histology for GPA (WG) could be obtained. Flexible bronchoscopy revealed diffuse erythema, edema of the mucosa and stenosis of the right mainstem bronchus. Transbronchial biopsy identified granuloma with giant cells. These findings led to a diagnosis of GPA (WG). This case suggests that biopsy from the bronchus is useful for diagnosis of GPA (WG).